Use of 4β‐Hydroxycholesterol Plasma Concentrations as an Endogenous Biomarker of CYP3A Activity: Clinical Validation in Individuals With Type 2 Diabetes. Issue 4 (5th June 2019) - Gravel, Sophie; Chiasson, Jean‐Louis; Gaudette, Fleur; Turgeon, Jacques; Michaud, Veronique
Abstract : The relevance of endogenous 4β‐hydroxycholesterol (4β‐OHC) plasma concentrations or of the 4β‐OHC/total cholesterol concentration ratio (4β‐OHC ratio) as surrogate markers of cytochrome P450 3A (CYP3A) activity was evaluated in individuals with ( n = 38) or without ( n = 35) type 2 diabetes (T2D). Midazolam was used as a comparator to validate exploratory measures of phenotypic CYP3A activity. Metabolic ratios of orally administered midazolam in nondiabetic and diabetic populations correlated significantly with 4β‐OHC ( r s = 0.64 and 0.48; P ≤ 0.003) and 4β‐OHC ratio ( r s = 0.69 and 0.46; P ≤ 0.003), respectively. Activity of CYP3A was lower in the T2D population compared with nondiabetic subjects; this decrease was reflected in 4β‐OHC concentrations (24.33 vs. 12.58 ng/mL; P < 0.0001) and 4β‐OHC ratio (0.13 vs. 0.09 (× 10 4 ); P < 0.0002). These results suggest that 4β‐OHC should be considered as a valid, convenient, and easy to use endogenous biomarker of CYP3A activity in patients.